The Disembodied Subject: Resistance to Norms of Hegemonic Identity Construction in Carmen Naranjo’s Diario de una multitud - Regan Boxwell (Studies in 20th & 21st Century Literature, 2013)
Costa Rica, whose civil war ended in 1948, represents a distinct literary space in which problematics of subjectivity were debated long before such dialectics appeared overtly in the rest of the isthmus. Carmen Naranjo’s novel Diario de una multitud (1974) is situated in this context, and her novel demonstrates a preoccupation with the heterogeneity of tico identity. Naranjo favors a collective representation of the urban citizenry. Through the perceptual liminality of the individual subject, the friction generated by its absence, the constant blurring that resets the boundaries of specific identities, and the disappearance of the private realm, Naranjo avoids inscribing lesbian desire. This novel has a disappeared lesbian. The urban multitudes are a spectacle of diversion that imply a mise en abyme of sexual desire, a speculation on the impossibility of liberating that desire. The blurred melancholy of the multitude replaces the blurred lesbian haunting the pages but never appearing in them. The splintered subjectivities, absence of sexual markers, and secretiveness of private lives imply the violence with which sexuality has been repressed. This study argues that denying embodiment to the subject(s) of Diario’s narration simultaneously obscures the lesbian and resists the violence that definition and even self-definition perpetrate on the subject.
Keywords: Costa Rica; Carmen Naranjo; disembodiment; lesbian identity; identity; collective identity; individual identity